PERAN KOMUNIKASI DALAM BUDAYA POLITIK (STUDI SISTEM POLITIK DINASTI ) - Risyat Albert Far Far (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2018)
Democracy  in  Indonesia  have  exams  with  the  emergence  of  the  phenomenon  of  political  dynasty.  The phenomenon of dynastic politics due to five things: first, the impact of the electoral system and the competition the more liberal. Second, the portrait of the failure of political parties in binding constituents .. Third, the lack of regeneration  system  and  internal  patterns  of  rekuitmen  in  political  parties,  especially  the  mechanism  in  the determination of candidates. Fourth, that too much traction power elites of political parties, especially the elite at central level. Fifth, the strengthening of political pragmatism and the decline of militancy cadre which causes the machine party organizations can not be optimal, and may encourage the proliferation of money politics and political  dynasties.  Atut  Chosiyyah  dynastic  political  system  is  legitimized  through  the  local  elections  and parochial political culture Banten people. Several factors are melatarbelakngi birth of prejudice in the election in  Banten  namely  the  lack  of  political  education  by  the  organizers  of  the  election,  the  election  supervisor, prospective  head  region  and  educational  institutions.  And  parochial  political  culture  inherited  money continuously to voters who incidentally have limited knowledge and political awareness. Atut Chosiyyah family group  has  a  network  of  warlords,  clerics  and  political  participants  widely  to  remote  allows  campaign  props scattered in almost every point in Banten. the amount and intensity of Banten people see props build closeness and sympathy of the public.Keywords: Political dynastiy, political culture money